Arbeitsgemeinschaft Prof. Dr. P. Roquette: 18. und 19. Mai 1968 - Roquette, Peter (Tagungsbericht, 1968)
G. Frey, Heidelberg; W. D. Geyer, Heidelberg; H. Göhner, Tübingen; U. Göhner, Heidelberg; P. Hahnel, Heidelberg; O. Herrmann, Heidelberg; K. Irion, Heidelberg; J. Leicht, Heidelberg; F. Lorenz, Heidelberg; G. Martens, Heidelberg; K. Radbruch, Tübingen; P. Roquette, Heidelberg; W. Schmale, Stuttgart; H. Sprung, Heidelberg